Ṭabaqāt al-Asy‘ariyyah fī Indūnīsiyā fī al-Qarnayn al-Khāmis ‘Asyar wa al-Sādis ‘Asyar al-Mīlādiyayn - Zahasfan, Alvian Iqbal (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
This research aims to know the Ash'ari scholars in Indonesia in the fifteenth and sixteenth centuries, in view of what was circulated among the people in Indonesia that the Nine Saints who contributed to the Islamization of the land of Java were the Ash'aris. In other words, the research wants to answer the question: Are the Nine Saints Ash’arite? Who are they and their classes? Therefore, the research attempts to achieve this and verify it according to an academic scientific method. The research is carried out with an integrated qualitative method, using a historical and analytical approach (heuristic), which collects all relevant data through induction, library research, documentation. It relies mainly on basic references such as the book Suluk Wujil and the book of Primbon Bonang by Sunan Bonang, and it also relies on second sources such as the book Atlas of the Nine Saints by the Indonesian historian Agus Sunyoto. This research is distinguished from other similar previous studies in its focus on revealing and investigating the ideology of the Nine Saints. The results reached by the research are that nine saints are of Ash'arism.